Towards the Development of Sustainable Supply Chains for the End-Of-Life Tires Management: Insights from a Literature Approach - Espinoza-Perez, A; Castañeda-Rodriguez, I (Springer Science and Business Media B.V., 2023)
Growing environmental concerns regarding pollution have led to legislation toughening worldwide to achieve mitigation. For example, in Chile, the extended producer responsibility (EPR) law makes producers responsible for waste management of the goods they market within the country. One of these goods is end-of-life tires (ELT) because of their high pollution potential. The EPR law establishes the goal of collecting 50% of common tires and a valorization of 25% by 2023, gradually increasing over the years. Thus, there is an opportunity to implement an ELT supply chain with valorization technologies to explore new energy alternatives and value-added products. This would contribute to a circular economy and national energy matrix decarbonization. Therefore, through a comprehensive literature review, this study aimed to identify the principal supply chain design challenges for ELT treatment through a sustainable approach. Twenty-five articles were reviewed and analyzed considering the sustainability dimensions addressed, the decision-making levels assessed, the type of ELT treatment, the network structure, the country of study, the inclusion of uncertainty, the optimization model proposed objective functions number, the solution method used, and authors’ analysis. The conclusions highlight the current research contributions and shortcomings and suggest possible directions for future work. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: End-of-life tire; Optimization; Sustainability